Analisis Kontribusi dan Efektivitas Pendapatan Asli Daerah Kota Bukittinggi Tahun 2011-2018 - Nita Atika; Rani Sofya (Jurnal Ecogen, 2020)
This research aims to determined the effectiveness and contribution of local revenues in the city of bukittinggi in 2011-2018. The type of research used is a descriptive research and using the analysis of contributions and analysis effectiveness. The type of data used was secondary data.Based on the research results obtained by the results of 1) the contribution of local taxes is in good criteria with an average of 42.40 percent. The effectiveness municipal tax is on the effective criteria with an average of 98.16 percent.2) the contribution of regional retribution is in the medium criteria with an average of 29.38 percent. The effectiveness of regional is on the effective criteria with an average of 99.52 percent. 3)contribution of the results of the management of separated regional wealth is in the very poor criteria with an average of 6.06 percent. The effectiveness of the results of the management of the separated regional wealth is in the very effective criteria with an average of 100.65 percent.  4) other legitimate local government revenue contributions local government revenue are in the medium criteria with an average of 22.16 percent. The effectiveness of other legitimate local government revenue is very effective with an average of 120.31 percent. For the future, the local government of bukittinggi should further optimize the management of the regional wealth separated in order to make a great contribution to the original revenue of the city of bukittinggi. Keywords : local goverment revenue, effectiveness and contribution